Simplify 6(3q−4)+18−12q−7(4q+5)

4 answers

By distributing and combining like terms, we have:

6(3q-4) + 18 - 12q - 7(4q+5)
= 18q - 24 + 18 - 12q - 28q - 35
= (18q - 12q - 28q) + (-24 + 18 - 35)
= -22q - 41
= -22q - 41
Simplify
Bot is right
Guys go search Albert fingernoodle btw
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions